The mail elements of the economy of knowledge (Economics and region, 2023)
The economy of knowledge as an important factor in the generation of wealth requires the creation of favorable legal and socio-economic conditions for the development of workers in the field of knowledge economy. The development of the knowledge economy is becoming necessary for Ukraine as a way to achieve innovative progress and increase the country's competitiveness. With the help of scientific literature, the authors studied the elements of the modern knowledge economy that help create developed and stable societies where knowledge and innovation play a key role, and highlighted the main ones: knowledge production, knowledge dissemination, knowledge implementation. Knowledge production facilities such as universities, laboratories, and research centers were studied. The spread of knowledge in a region depends on many factors, including social, technical and institutional infrastructure, as well as human capital. The interaction of these factors is important. The network approach to interaction between various subjects of knowledge dissemination, such as technology transfer centers, science and technology parks, business incubators, clusters, is analyzed. The authors emphasize the main factors of production in the new paradigm of regional development: human capital, innovation, access to information and communications, cooperation and exchange of knowledge, flexibility and adaptability. It has been established that social, technical and institutional infrastructure, as well as human capital, are factors that influence the spread of knowledge in the region. The interaction of the factors consists in cooperation between sectors, access to technology, education and development of human capital, culture of innovation and innovation system, which provide a favorable environment for the development and dissemination of knowledge in the region, and also affect economic development and improvement of the quality of life of the population. As a result, it is proposed to highlight the following elements of the knowledge economy: knowledge production, knowledge dissemination and knowledge implementation, which play an important role in the scientific and technical sphere.
Keywords: knowledge economy; elements; production; distribution; introduction of knowledge; factors; subjects; human capital; innovations; communications; knowledge exchange; universities; clusters; intellectual property